Chemical Constituents of the Leaves of Diospyros kaki (Persimmon) - Jaeyoung Kwon; Jeong-Eun Park; Jin-Su Lee; Jung-Hwan Lee; Hoseong Hwang; Sang-Hoon Jung; Hak-Cheol Kwon; Dae-Sik Jang (Plants, 2021)
Diospyros kaki (persimmon) leaves have long been utilized as traditional medicine for the treatment of ischemic stroke, angina, and hypertension and as a healthy beverage and cosmetic for anti-aging. This study aimed to isolate as many compounds as possible from an ethanol extract of the persimmon leaves to identify the biologically active compounds. The antioxidative effect of the ethyl acetate layer from the ethanol extract of the persimmon leaves was demonstrated by 2,2-diphenyl-1-picrylhydrazyl (DPPH) assay and online high-performance liquid chromatography-2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) (HPLC-ABTS) analysis. A new flavonoid, kaempferol-3-O-β-d-2″-coumaroylgalactoside (1), and a new natural compound, kaempferol-3-O-β-d-2″-feruloylglucoside (3) were isolated from the ethyl acetate layer, along with 25 previously known compounds, including fourteen flavonoids, one ionone, two coumarins, seven triterpenoids, and one acetophenone. Their structures were determined by the interpretation of spectrometric and spectroscopic data. All isolated compounds were rapidly evaluated using an online HPLC-ABTS assay, and of these, compounds 4–8, 11, 13, 15, and 16 clearly showed antioxidative effects. The amount of these compounds was 0.3–0.65% of the extract.